Water-sensitive in-situ ultrafast self-gel styptic powder as well as preparation method and application thereof
By using water-sensitive in-situ ultrafast autogel hemostatic powder composed of grafted thiol gelatin and grafted catechol group hyaluronic acid, the problem of limited application of existing hemostatic materials in incompressible internal bleeding is solved, and the effect of rapid hemostatic, enhanced tissue adhesion and reduced inflammatory response is achieved.
Patent Information
- Application Number
- CN202510001400.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing hemostasis materials are limited in application in incompressible internal bleeding (such as heart, liver, and cerebral hemorrhage), and light hemostasis powder is difficult to firmly adhere to severe bleeding wounds, making it impossible to achieve a complete sealing effect.
Water-sensitive in-situ ultrafast self-gel hemostatic powder composed of grafted thiol gel and grafted catechol group hyaluronic acid is used to quickly form chemically cross-linked hydrogels by absorbing interface water, enhancing adhesion strength with tissues.
A hydrogel that forms chemically crosslinked in situ by absorbing interface water within 5 seconds is achieved. It has excellent blood absorption and tissue adhesion, can quickly stop bleeding, close broken incisions, reduce inflammatory response, and accelerate wound healing.
Smart Images

Figure CN119746139A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a water-sensitive in-situ ultrafast self-gelling hemostatic powder, belonging to the field of biomaterials. Background Art
[0002] Uncontrolled bleeding after severe tissue trauma is one of the main fatal causes of military and civilian casualties. Timely hemostasis and wound suturing are the key to reducing bleeding and effectively improving survival rate. Conventional methods such as suturing and staplers are clinically regarded as the gold standard for wound closure and hemostasis, but they are not suitable for on-site emergency trauma treatment due to preoperative anesthesia, long operation time, and secondary tissue damage. In addition, infected traumatic bleeding and tissue damage, such as bleeding during burn surgery, have anti-infection and regeneration requirements. Therefore, in order to meet the increasingly urgent clinical needs, it is necessary to develop multifunctional hemostatic materials with rapid hemostasis, good adhesion, good mechanical properties as a cover for the hemostatic site to maintain blood pressure, biocompatibility that meets the requirements, good anti-infection ability, and the ability to promote healing.
[0003] The main hemostatic materials at present are gauze, sponges, hydrogels and powders. Traditional gauze and sponges mainly stop bleeding by absorbing fluid in the blood to concentrate coagulation factors. Various hemostatic hydrogels based on natural or synthetic materials have been developed for incompressible, irregular, deep, narrow or perforated wounds due to their excellent fluidity and shape plasticity. It is worth noting that the hemostatic powder composed of tiny particles can not only completely cover and penetrate into irregular, narrow, deep, incompressible bleeding wounds to obtain rapid hemostasis in a short time, but also quickly hydrate and form gel in situ to achieve the purpose of wound sealing and anti-contaminant. At present, many self-gelling powders have been recently developed, which can quickly form in situ hydrogels after hydration and effectively seal bleeding wounds. For example, Bian et al. reported an ultra-fast self-gelling wet-adhesive polyimide / polyacrylic acid / quaternized chitosan (PEI / PAA / QCS) powder as a hemostatic material and wound dressing. The PEI / PAA / QCS powder is deposited on the bleeding wound and can quickly absorb a large amount of blood and concentrate coagulation factors. At the same time, the powder can form an adhesive hydrogel in situ within 4 seconds after hydration, forming a pressure-resistant physical barrier.
[0004] Frequent replacement of gauze and compression of bleeding sites limit its application in incompressible internal bleeding (such as heart, liver, and brain bleeding). Despite the rapid development of adhesive hydrogels, the problem of wet adhesion performance to achieve rapid tissue adhesion and hemostasis under flowing blood remains to be solved.
[0005] Application number 202210558775.5, invention name: A hemostatic, antibacterial and healing-promoting hydrogel with real-time monitoring function and preparation method, a hemostatic, antibacterial and healing-promoting hydrogel with real-time monitoring function and preparation method, using natural polysaccharides as the main raw materials, by sequentially quaternizing, double-bonding and polyphenol grafting modification of polysaccharides and compounding inorganic nanoparticles and color-developing substances, a composite hydrogel is obtained, the obtained hydrogel can be injected into the bleeding or wound site by a syringe, and can quickly gel after light exposure, which can realize real-time monitoring of the inflammatory response of the wound site, and can promote hemostasis and wound healing of the bleeding site. This patent document uses polyphenol grafted double-bond quaternized polysaccharide to load inorganic nanomaterials, and forms a hydrogel dressing through photoinduced crosslinking. It is necessary to prepare a prepolymer solution and then photocrosslink it. The application conditions are complicated, and it is impossible to achieve hemostasis for situations such as heavy bleeding. Because it contains a large amount of water, the amount of blood absorbed is limited, and due to the presence of interfacial water, the tissue adhesion is usually poor, and effective sealing cannot be achieved.
[0006] Application number: CN202310516735.9, invention name: Preparation method and application of a body temperature induced adhesive gelatin-based hydrogel, discloses a preparation method and application of a body temperature induced adhesive gelatin-based hydrogel, and belongs to the technical field of biomedical polymer materials. This patent is to crosslink the natural polysaccharide grafted with thiol and gelatin grafted with thiol with silver ions and load natural active small molecules to finally obtain a multifunctional hydrogel. The hydrogel is mainly used for wound healing. The gel is constructed by a double network, one is a coordination network crosslinked with silver ions, and the other is a physical crosslinked network of gelatin; wherein the gelatin network has strong tissue adhesion at body temperature (37°C), but no tissue adhesion at low temperature (5°C), so the hydrogel dressing can be easily removed as needed. The patent discloses a hydrogel dressing formed by photoinduced crosslinking of thiol mechanism polysaccharides crosslinked with silver ions and gelatin loaded with active small molecules, which realizes wound regeneration by being used as a hydrogel dressing, and it is only used as a wound dressing, and the hemostatic function of the wound cannot be achieved. In addition, the prepared hydrogel cannot achieve hemostasis in situations such as heavy bleeding because it contains a large amount of water, so the amount of blood absorbed is limited. Moreover, due to the presence of interfacial water, tissue adhesion is usually poor and effective sealing cannot be achieved.
[0007] The current lightweight hemostatic powder still cannot firmly adhere to a severely bleeding wound to achieve a complete sealing effect, and may even dissolve or diffuse into the blood, increasing the risk of vascular embolism. In addition, the main component of the hemostatic powder is a synthetic polymer, which is characterized by a long degradation time and lack of biological activity. Summary of the invention
[0008] The technical solution of the present invention is to provide a water-sensitive in-situ ultrafast self-gel hemostatic powder, which is a multifunctional bionic hemostatic powder and is particularly suitable for incompressible internal hemostasis.
[0009] The present invention provides a water-sensitive in-situ ultrafast self-gelling hemostatic powder, which is prepared by mixing and low-temperature grinding the following raw materials in the following weight ratio:
[0010] 1-2 parts of gelatin grafted with mercapto groups and 1-2 parts of hyaluronic acid grafted with catechol groups.
[0011] Preferably, it is prepared by mixing and cryogenically grinding the following raw materials in the following weight ratios:
[0012] 1 part of grafted mercapto gelatin, 1-2 parts of hyaluronic acid grafted with catechol groups, and 1 part.
[0013] The grafted thiol gelatin is prepared using gelatin and cysteamine hydrochloride as raw materials and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) as catalysts;
[0014] The hyaluronic acid grafted with catechol groups is prepared by using hyaluronic acid and dopamine as raw materials and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) as catalysts.
[0015] Preferably, in the preparation method of grafted thiol gelatin, the mass ratio of gelatin, cysteamine hydrochloride, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) is:
[0016] 1 part of gelatin, 1.86 parts of cysteamine hydrochloride, 4.81 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), and 2.93 parts of N-hydroxysuccinimide (NHS);
[0017] In the preparation method of the hyaluronic acid grafted with catechol groups, the mass ratio of hyaluronic acid, dopamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) is:
[0018] 1 part of hyaluronic acid, 1.2 parts of dopamine, 1.8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), and 0.73 parts of N-hydroxysuccinimide (NHS).
[0019] Wherein, the preparation method of the grafted thiol gelatin is:
[0020] The gelatin was completely dissolved in deionized water at 60°C, then cooled to room temperature, EDC, NHS and cysteamine hydrochloride were added in sequence, the pH value of the solution was adjusted to 5 using 1M sodium hydroxide and hydrochloric acid, and the reaction was allowed to proceed overnight; finally, the purified dialysate was centrifuged to remove insoluble impurities, and the supernatant was freeze-dried to obtain the grafted thiol gelatin;
[0021] The preparation method of the hyaluronic acid grafted with catechol groups is as follows:
[0022] HA is dissolved in deionized water, followed by the addition of EDC and NHS, with the pH value maintained between 4.75 and 5.0; under nitrogen protection, dopamine DOPA-HCl dissolved in deionized water is added to the reaction mixture, and the pH value is maintained between 4.75 and 5.0 for 12 hours; thereafter, the reaction solution is dialyzed with deionized water for three days to remove unreacted reagents and by-products; finally, the solution is freeze-dried to obtain hyaluronic acid grafted with catechol groups.
[0023] The present invention provides a method for preparing the water-sensitive in-situ ultrafast self-gelling hemostatic powder, which comprises the following steps:
[0024] a. Weigh the thiol-grafted gelatin and the hyaluronic acid grafted with catechol groups in respective weight ratios;
[0025] b. Mix, add to low-temperature grinder and grind.
[0026] The grinding conditions are: grinding at a frequency of 30 Hz for 15 minutes.
[0027] The invention provides use of the water-sensitive in-situ ultrafast self-gel hemostatic powder in preparing an external medicine with hemostatic effect.
[0028] The water-sensitive in-situ ultrafast self-gelling hemostatic powder of the present invention can form a chemically cross-linked hydrogel in situ by absorbing interfacial water within 5 seconds, and has excellent blood absorption. The sulfhydryl and catechol groups can be cross-linked with the amino groups on the tissue surface, further improving the adhesion strength of the powder to the tissue. The need for additional bandages or sutures is reduced. In addition, the hemostatic powder designed based on biomimetic extracellular matrix components has good biocompatibility and has a certain clearing effect on inflammation. In a rat model of total skin defect, the powder can not only stop bleeding quickly and seal damaged incisions, but also reduce inflammatory reactions and accelerate wound healing. The materials of the hemostatic powder of the present invention are cross-linking achieved by reactions between sulfhydryl-sulfhydryl, sulfhydryl-dopamine, and dopamine quinone oxide-amino groups. By spraying the powder on the wound surface, it absorbs blood, forms gel in situ, and forms tissue adhesion to achieve hemostasis and repair. The dry powder can effectively absorb interfacial water, enhance adhesion to tissues, and is easier to make into commercial products. The prepared powder can be stored for a long time and can be used as soon as it is opened. In short, the hemostatic powder of the present invention combines the characteristics of rapid water absorption, strong adhesion and biocompatibility, making it an ideal candidate for a wide range of medical applications, including hemostasis, wound sealing and tissue regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 .Preparation and characterization of GSHD powder. (A) Fourier transform infrared spectra and (B) 1H NMR spectra of Gel-SH and HA-DA. SEM image (C) and particle size distribution (D) of Gel-SH. Scale bar = 10 μm. SEM image (E) and particle size distribution (F) of HA-DA. Scale bar = 10 μm. (G) Schematic diagram of powder preparation using a convenient liquid nitrogen-assisted mechanical grinding method. (H) Evaluation of PBS absorption of GSHD hydrogel and GSHD powder. (I) Liquid absorption rate (%) of GSHD hydrogel and GSHD powder in PBS and blood (n = 3);
[0030] Figure 2. Rapid gelling transformation, tissue wetting and sealing of GSHD powders. (A) Storage modulus (G′) and loss modulus (G″) of GS1HD2, GH1HD1 and GS2HD1 as a function of frequency. (B) Stress-strain curves in compression test and (C) compressive strength (KPa) of three groups (n=3). (D) Rheological curves of three groups in alternating step strain sweep mode. (F) Shape adaptability of GS1HD1 evaluated by “S”, “C” and “U” shape models. (G) Self-gelling effect in blood illustrated by inverted tube method. (H) GS1HD1 fixed on glass adheres to wet porcine skin in a short time. (I) Porcine skin adhered to GS1HD1 by water flushing. (J) SEM images of bonding interface, scale bar = 30 μm. (L) Bonding strength (KPa) and (M) burst pressure (mmHg) of GS1HD2, GS1HD1 and GS1HD2 (n=3);
[0031] Figure 3 .Biocompatibility and antioxidant properties of GSHD powder. Live / dead staining images of (A) NIH-3T3 and (B) L929 cells after incubation with GSHD powder for 1, 3, and 5 days. Scale bar, 200 μm. Cell viability of (C) NIH-3T3 and (D) L929 cells after incubation with GSHD powder for 1, 3, and 5 days was assessed by MTT assay (n=3). Immunofluorescence staining of (E) IL-6 and (F) IL-10. Scale bar, 200 μm (ns: no significant difference);
[0032] Figure 4 : Blood compatibility and hemostatic properties of GSHD powder. Blood compatibility and hemostatic properties of GSHD powder. (A) Hemolysis test and (B) hemolysis ratio of HA-DA, Gel-SH and GSHD powders. (C) Schematic diagram of inducing rat liver bleeding and using GSHD powder to stop bleeding. (D) Photographs of bleeding and hemostasis after using GSHD powder. (E) Quantification of liver hemostasis time and blood loss (n=3). (F) Photographs of acute bleeding and hemostasis caused by using GSHD powder in rat tail vein, (G) rat heart and (H) rat femoral artery bleeding models;
[0033] Figure 5.In vivo skin incision adhesion and sealing properties of GSHD powder. (A) Schematic diagram of full-thickness skin incisions in rats treated with GSHD powder. (B) Experimental images and (C) wound healing rates of skin incisions in different treatment groups (n=3). Scale bar, 1 cm. (D) H&E staining images showing tissue recovery of incisions in different treatment groups on day 14. Scale bar, 200 μm. (E) Masson's trichrome staining images showing collagen recovery of incisions in different treatment groups on day 14. Scale bar, 200 μm. (F) Immunofluorescence staining images of IL-6 and (G) TNF-α in different treatment groups on day 14 to assess inflammatory infiltration. Scale bar, 100 μm. DETAILED DESCRIPTION
[0034] Example 1 Preparation of the water-sensitive in-situ ultrafast self-gelling hemostatic powder of the present invention
[0035] Preparation of Gel-SH: 1 g of gelatin was completely dissolved in 100 ml of deionized water at 60°C, then cooled to room temperature, and EDC (4.81 g), NHS (2.93 g) and cysteamine hydrochloride (1.86 g) were added in sequence. The pH value of the solution was adjusted to 5 using 1 M sodium hydroxide and hydrochloric acid, and reacted overnight. Finally, the purified dialysate was centrifuged to remove insoluble impurities, and the supernatant was lyophilized to obtain Gel-SH.
[0036] Preparation of HA-DA: 1 g of HA was dissolved in 100 ml of deionized water. EDC (1.8 g) and NHS (0.73 g) were then added, and the pH was maintained between 4.75 and 5.0. Under nitrogen protection, 1.2 g of dopamine DOPA-HCl dissolved in 50 ml of deionized water was added to the reaction mixture, and the pH was maintained between 4.75 and 5.0 for 12 hours. Afterwards, the reaction solution was dialyzed with deionized water for three days to remove unreacted reagents and by-products. Finally, the solution was lyophilized to obtain HA-DA.
[0037] Preparation of GSHD powder and its hydrogel: Freeze-dried Gel-SH and HA-DA were added to a cryogenic grinder and ground at a frequency of 30 Hz for 15 minutes to obtain fine and uniform Gel-SH and HA-DA powders, respectively. GS1HD2, GS1HD1, and GS2HD1 powders were prepared by mixing quantitative Gel-SH and HA-DA powders in a mass ratio of 1:2, 1:1, and 2:1, respectively. The prepared powders were stored in a dry environment.
[0038] PBS solution was added into GSHD powder for self-gelation to prepare GSHD hydrogel control group.
[0039] Example 2 Preparation and Characterization of GSHD Powder
[0040] In order to obtain components with biomimetic extracellular matrix composition, Gel-SH (gelatin grafted with thiol groups) and HA-DA (hyaluronic acid grafted with catechol groups) were first synthesized. Specifically, thiol groups and catechol groups were introduced into gelatin and hyaluronic acid, respectively, by amidation reaction catalyzed by EDC / NHS. Fourier transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance (NMR) 1 The chemical structures of Gel-SH and HA-DA were evaluated by Fourier transform infrared spectroscopy (H NMR). Figure 1 A), 1553cm -1 and 1613cm -1 The peak at 1731 cm -1 The peaks at 1630 and 1540 cm represent phenolic hydroxyl groups. Similarly, amide bond peaks (1630 and 1540 cm -1 ) and thiol at 970 cm -1 The bending vibration peak at Figure 1 As shown in Figure B, the proton peaks (δ = 6.8, 6.9 ppm) in HA-DA and the peak (δ = 3.13 ppm) in the Gel-SH spectrum further confirmed the successful grafting of the functional groups. The preparation of Gel-SH and HA-DA powders adopted a convenient liquid nitrogen-assisted mechanical grinding method, which is conducive to large-scale production and product conversion ( Figure 1 G). Scanning electron microscope image ( Figure 1 C&E) showed that the shape of the powder was mainly irregular polyhedron. Further statistics showed that the size distribution of the ground powder was very wide. The median particle size (D50, the corresponding particle size when the cumulative particle size distribution percentage of the sample reached 50%) of Gel-SH and HA-DA powders was 31 and 40 μm, respectively, showing a smaller particle size ( Figure 1 D&F). As we all know, powdered hemostatic materials are widely used because of their advantages such as adaptability to the irregular topography of wounds and high water absorption. Therefore, we mainly evaluated the water absorption capacity between different forms (hydrogel and powder) of the same material. Figure 1 H shows that the same weight of GSHD hydrogel and powder absorbed 300 μL of dyed PBS. Unlike the residual PBS in the hydrogel group, the powder-type material absorbed PBS within 1 minute. The liquid absorption behavior of GSHD hydrogel and powder in PBS and blood was also evaluated. Figure 1 The results in I showed that the absorption rates of GSHD powder to PBS and blood were 518.3±50.7% and 569.2±46.3%, respectively, while those of the GSHD hydrogel control group were 26±5% and 31.4±3.6%, respectively.
[0041] The powder is composed of natural biopolymers and is rich in hydrophilic groups such as hydroxyl, amino, and carboxyl groups. Compared with hydrogels, it has a larger specific surface area and therefore has excellent liquid absorption capacity and is suitable for the treatment of massive bleeding.
[0042] Example 3 Rapid gelling transformation, tissue wet bonding and sealing of GSHD powder
[0043] After absorbing blood, the thiol and catechol groups in the powder will undergo a click reaction and quickly transform into a stable gel-like structure. It not only forms a physical barrier to prevent blood from flowing out, but also prevents the powder from entering the blood, thereby reducing the risk of other complications during the use of the material.
[0044] In order to better understand the effect of powder component content on structure and performance, we set up three groups of different powder compositions. According to the different contents of Gel-SH and HA-DA in GSHD powder, three groups of powders were designed: GS1HD2 (Gel-SH is 20 mg, HA-DA is 40 mg), GS1HD1 (Gel-SH is 30 mg, HA-DA is 30 mg) and GS2HD1 (Gel-SH is 40 mg, HA-DA is 20 mg). The mass ratios were 1:2, 1:1 and 2:1, respectively. The final mass of each group of powder was 60 mg. First, the mechanical properties of the powder after self-gelation were evaluated using a rheometer. In sweep mode ( Figure 2 A), the hydrogel formed after self-gelation exhibits typical viscoelastic behavior, characterized by a storage modulus (G') greater than the loss modulus (G'). The G' of GS1HD1 is 2448 Pa, which is about 2.89 times and 1.48 times that of GS1HD2 and GS2HD1, respectively, indicating that a denser hydrogel network is formed in the GS1HD1 powder. Figure 2 As shown in Figures B and 2C, the compressive strengths of GS1HD2, GS1HD1, and GS2HD1 are 23.72±5.88, 40.55±3.31, and 25.61±4.67 KPa, respectively, which indicates that the powder can form a strong three-dimensional network structure after absorbing water, which has a conductive effect on resisting external stress. The morphology of the hydrogel after self-gelation was further observed by scanning electron microscopy, as shown in Figure 2 Figure 2 As shown in Figure D, GS1HD1 formed a more uniform and clear pore structure, which is conducive to exerting better hemostatic performance. In order to apply the hydrogel to the situation of heavy bleeding and solve the damage that may be caused by blood pressure, tearing and external force, we further explored the self-healing behavior of GS1HD2, GS1HD1 and GS2HD1. Figure 2As shown in E, the hydrogel network is maintained under low strain (1%) conditions (G'>G"), while the hydrogel network is damaged under excessive strain (200%) conditions (G'<G"), and during the alternation of large and small strains, the integrity of the hydrogel can be repeatedly restored. This self-healing behavior may be attributed to the dynamic thiol-catechol cross-linking reaction. In addition, to test the shape adaptability of the hydrogel, we also used "S", "C", and "U" shaped models to simulate irregular and deeper wound surfaces, which is more similar to the actual situation. As Figure 2 shown in F, after removing the models of different shapes, all samples maintained their original intact shape without damage, mainly due to the rapid self-gelation and self-healing ability of the powder. To verify the self-gelation effect of the powder on blood, we took GS1HD1 as an example to conduct an inverted tube method experiment. As Figure 2 shown in G, after putting GS1HD1 into a test tube filled with blood, it immediately absorbed a large amount of liquid. After inverting the test tube for 5 seconds, GS1HD1 had transformed into a hydrogel, forming a complete liquid flow barrier.
[0045] Tissue wet adhesion is very important in bleeding treatment. Figure 2 H mainly shows the evaluation of wet bioadhesion effect using pig skin. To create a wet environment, PBS and GS1HD1 powder were added to the pig skin. Interestingly, the pig skin was lifted by the glass slide within 6 seconds, which proved good tissue wet adhesion. In addition, considering the use in severe bleeding situations, the hemostatic powder will be impacted by rapidly flowing blood. Figure 2 I evaluated the anti-blood scouring ability of the powder. The self-gelled powder can tightly adhere to the tissue even under severe water flow scouring. Scanning electron microscopy observed the tight adhesion at the hydrogel-tissue interface, showing a tight connection under the microscope ( Figure 2 J).
[0046] To quantitatively evaluate tissue adhesion, a lap shear test was conducted. In Figure 2 L, the adhesion strength of GS1HD1 was as high as 28.29±2.98 KPa, significantly higher than the other two groups of powders. In addition, a burst test was also used to determine the tissue sealing ability. After stabilizing for 30 minutes, an injection pump was used to increase the burst pressure. As Figure 2As shown in Figure 2, the burst pressure of GS1HD1 is 216.25±10.5 mmHg, which is nearly twice that of GS1HD2 and GS2HD1, indicating that it has stronger resistance to blood flushing. In addition, the burst pressure of tGS1HD1 is even higher than the normal systolic blood pressure of the human body (120 mmHg), which may be related to the optimal cohesion and adhesion of GS1HD1. In the above experiments, GS1HD1 obtained the best adhesion strength and burst pressure, which indicates that the appropriate combination of thiol and catechol groups can produce more adhesion sites and form stronger chemical crosslinks with tissues. In summary, our self-adhesive powder has excellent self-healing, shape remodeling, rapid self-adhesion and strong wet tissue adhesion properties, which are very suitable for wound hemostasis and sealing.
[0047] The beneficial effects of the present invention are demonstrated by efficacy tests as follows.
[0048] Test Example 1 Cytocompatibility and Antioxidant Properties of GSHD Powder
[0049] As a biomaterial used for wound hemostasis and sealing, it is crucial to evaluate its biocompatibility. To evaluate the cytocompatibility of the material, we used MTT assay and live / dead staining to evaluate cell proliferation and cell growth activity. Figure 3 As shown in A and B, after 1, 3 and 5 days of co-culture of NIH-3T3 and L929 mouse fibroblasts with GSHD powder materials, the cell growth activity was very high, and almost no dead cells were observed by PI staining. MTT test results ( Figure 3 C&D) showed that the proliferation capacity of cells co-cultured with GSHD powder was comparable to that of the control group, with no statistically significant difference. These results indicate that the powder has good in vitro biocompatibility and can maintain the normal physiological state of cells.
[0050] During wound healing, macrophages play a key role in regulating immune responses and inflammation. M1 macrophages have pro-inflammatory properties, while M2 macrophages secrete anti-inflammatory cytokines and regulate the production of extracellular matrix, which has anti-inflammatory properties. During wound repair, the phenotypic conversion of macrophages from M1 to M2 is often blocked, resulting in persistent inflammatory responses and delayed wound healing. Therefore, materials used for wound healing should have excellent inflammation regulation capabilities and promote the polarization of macrophages from M1 to M2 phenotypes, thereby accelerating wound healing. Surprisingly, GSHD powder contains catechol molecules, which have the potential to scavenge free radicals and alleviate oxidative stress, thereby potentially regulating the behavior of macrophages. To evaluate the effects of GSHD powder on macrophage polarization and inflammation regulation, we evaluated the expression of interleukin-6 (IL-6) and interleukin-10 (IL-10) using immunofluorescence staining. As Figure 3As shown in E and F, the fluorescence intensity of the pro-inflammatory cytokine IL-6 decreased in the GSHA powder-treated group compared with the control group, while the fluorescence intensity of the anti-inflammatory cytokine IL-10 increased. This may be due to the grafted catechol groups in the powder, which give it a good anti-inflammatory effect in vitro.
[0051] Test Example 2 Blood Compatibility and Hemostatic Properties of GSHD Powder
[0052] The ideal hemostatic powder should have good blood compatibility. When the hemostatic powder comes into contact with a bleeding wound, it should not or rarely induce a hemolytic reaction. Therefore, we need to evaluate the blood compatibility of GSHD powder by in vitro hemolysis test. 0.1% Triton-X 100 was used as the positive control group. After incubation with different materials, the supernatant of each group was collected by centrifugation ( Figure 4 A). The hemolysis rates of the HA-DA group, Gel-SH group, and GSHD group were all lower than 5% ( Figure 4 B). Therefore, the prepared GSHD powder material meets the safety standards of hemostatic materials.
[0053] The in vivo hemostatic properties of GSHD powder were evaluated using a rat liver bleeding model ( Figure 4 C) Figure 4 As shown in D and 4E, the injured liver of the untreated control rats was severely bleeding, forming a large blood stain on the filter paper. The bleeding time was about 120 seconds, and the blood loss was about 100 mg. In contrast, after applying GSHD powder to the bleeding site, it only took 28 seconds to stop bleeding, and the blood loss was significantly reduced to 30 mg. Compared with the untreated control group, the bleeding time and blood loss were reduced by about 75% and 70%, respectively, indicating that GSHD powder can quickly control bleeding.
[0054] We further applied the rat tail vein, heart, and femoral artery bleeding models to evaluate the in vivo hemostatic properties of GSHD powder in irregularly shaped and incompressible acute bleeding wounds. The rat tail was removed to induce acute bleeding in the tail vein, and then GSHD powder was placed on the wound surface. It immediately self-gelled in situ and adhered firmly to the bleeding site. It quickly absorbed blood and achieved hemostasis within 30 seconds ( Figure 4 F). Similarly, the rat heart and femoral artery were exposed and punctured to induce acute bleeding ( Figure 4 G and 4H). The use of GSHD powder can achieve rapid and effective hemostasis, sealing the bleeding site within 30 seconds. After hemostasis, these bleeding sites will not bleed again even if stretched. The above results show that GSHD powder can effectively play a hemostatic function and prevent secondary bleeding ( Figure 4 H). In summary, GSHD powder can effectively stop bleeding and avoid secondary bleeding.
[0055] Experimental Example 3 In vivo wound healing performance of GSHD powder on rat skin incision model
[0056] Given the excellent tissue adhesion and rapid hemostatic sealing properties of GSHD, we further used a rat full-thickness skin incision model to investigate the wound sealing effect of GSHD powder ( Figure 5 A). A 2 cm long skin incision was made on the back of the rat and then treated with glue adhesive, surgical sutures or GSHD powder. Figure 5 As shown in B, the skin incisions in the untreated control group became larger on the first day due to the rats' frequent natural activities. In contrast, the groups treated with glue adhesive, surgical sutures, and GSHD powder achieved incision closure on the first day. By the 14th day after surgery, the incisions in the GSHD powder group and the surgical suture group had healed without scar formation, with a wound closure rate of more than 60% ( Figure 5 C) Although the wound closure effects were similar in the surgical suture group and the GSHD powder-treated group, the GSHD powder-treated group achieved seamless closure of the damaged tissue, avoiding secondary injury.
[0057] Histological analysis was performed on postoperative day 14 to evaluate the wound healing status. Hematoxylin and eosin (H&E) staining confirmed the wound healing effect of GSHD powder ( Figure 5 D). Incisions treated with GSHD powder showed re-epidermal regeneration and new skin appendages, such as hair follicles and sebaceous glands. In contrast, untreated control incisions showed a significantly unrestored dermis with no skin appendages. Cavitation was still observed at the incision site in the glue-adhesive-treated group. The healing effect in the surgical suture group was relatively good; however, the presence of the sutures prevented complete regeneration of the dermis. Collagen deposition in the healing tissue was assessed using Masson's trichrome staining ( Figure 5 E). On day 14, the untreated control group had minimal collagen deposition at the incision site. The collagen fibers in the glue adhesive-treated group and the surgical suture group were poorly developed and loosely arranged. In contrast, the collagen fibers in the GSHD powder-treated group had regular orientation and a dense structure, similar to normal skin.
[0058] Immunostaining of proinflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) was performed on the 14th day after surgery ( Figure 5 F and 5G). The untreated control group had higher levels of IL-6 and TNF-α secretion, indicating a severe inflammatory response. The GSHD powder-treated group had the lowest levels of IL-6 and TNF-α at the skin incision, indicating that GSHD powder can effectively reduce the inflammatory response. In summary, GSHD powder can effectively promote wound sealing and tissue regeneration in full-thickness skin incisions in rats.
[0059] The present invention proposes a multifunctional biomimetic hemostatic powder based on an extracellular matrix (ECM)-derived biopolymer, which is composed of gelatin (Gel-SH) grafted with thiol groups and hyaluronic acid (HA-DA) grafted with catechol groups. These components can quickly form a chemically cross-linked hydrogel in situ by absorbing interfacial moisture within 5 seconds, thereby achieving rapid hemostasis and wound sealing. After rapid blood absorption, the thiol and catechol groups on the GSHD powder can form covalent bonds with the amino groups on the tissue surface, further enhancing the adhesion strength. Vertical shear and burst pressure tests show that the adhesion strength of the GSHD powder after self-gelation is 28.3±3Kpa, and it can withstand a burst pressure of up to 216.5±10mmHg. In addition, the powder also has good biocompatibility and anti-inflammatory properties. In a rat full-thickness skin defect model, the powder can not only quickly stop bleeding and seal the wound, but also reduce inflammatory reactions and accelerate wound healing. Therefore, we believe that GSHD powder is a hemostatic material and wound dressing with broad application prospects due to its strong adhesion, good biocompatibility, rapid hemostasis, suitability for non-compressible sites and wound sealing properties.
Claims
1. A water-sensitive in-situ ultrafast self-gelling hemostatic powder, characterized in that: It is made by mixing and low temperature grinding the following raw materials in the following weight ratio: 1-2 parts of gelatin grafted with mercapto groups and 1-2 parts of hyaluronic acid grafted with catechol groups.
2. The water-sensitive in-situ ultrafast self-gelling hemostatic powder according to claim 1, characterized in that: It is made by mixing and low-temperature grinding the following raw materials in the following weight ratio: 1 part of grafted mercapto gelatin, 1-2 parts of grafted catechol group hyaluronic acid, 1 part.
3. The water-sensitive in-situ ultrafast self-gelling hemostatic powder according to claim 1 or 2, characterized in that: The grafted thiol gelatin is prepared with gelatin and cysteamine hydrochloride as raw materials and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) as catalysts; The hyaluronic acid grafted with catechol groups is prepared by using hyaluronic acid and dopamine as raw materials and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) as catalysts.
4. The water-sensitive in-situ ultrafast self-gelling hemostatic powder according to claim 3, characterized in that: In the preparation method of grafted thiol gelatin, the mass ratio of gelatin, cysteamine hydrochloride, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) is: 1 part of gelatin, 1.86 parts of cysteamine hydrochloride, 4.81 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), and 2.93 parts of N-hydroxysuccinimide (NHS); In the preparation method of the hyaluronic acid grafted with catechol groups, the mass ratio of hyaluronic acid, dopamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) is: 1 part of hyaluronic acid, 1.2 parts of dopamine, 1.8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), and 0.73 parts of N-hydroxysuccinimide (NHS).
5. The water-sensitive in-situ ultrafast self-gelling hemostatic powder according to claim 3 or 4, characterized in that: The preparation method of the grafted thiol gelatin is as follows: The gelatin was completely dissolved in deionized water at 60°C, then cooled to room temperature, EDC, NHS and cysteamine hydrochloride were added in sequence, the pH value of the solution was adjusted to 5 using 1M sodium hydroxide and hydrochloric acid, and the reaction was allowed to proceed overnight; finally, the purified dialysate was centrifuged to remove insoluble impurities, and the supernatant was freeze-dried to obtain the grafted thiol gelatin; The preparation method of the hyaluronic acid grafted with catechol groups is as follows: HA is dissolved in deionized water, followed by the addition of EDC and NHS, with the pH value maintained between 4.75 and 5.0; under nitrogen protection, dopamine DOPA-HCl dissolved in deionized water is added to the reaction mixture, and the pH value is maintained between 4.75 and 5.0 for 12 hours; thereafter, the reaction solution is dialyzed with deionized water for three days to remove unreacted reagents and by-products; finally, the solution is freeze-dried to obtain hyaluronic acid grafted with catechol groups.
6. A method for preparing the water-sensitive in-situ ultrafast self-gelling hemostatic powder according to any one of claims 1 to 5, characterized in that: It includes the following steps: a. Weigh the thiol-grafted gelatin and the hyaluronic acid grafted with catechol groups in respective weight ratios; b. Mix, add to low-temperature grinder and grind.
7. The method for preparing the water-sensitive in-situ ultrafast self-gelling hemostatic powder according to claim 6, characterized in that: The grinding conditions are: grinding at a frequency of 30 Hz for 15 minutes.
8. Use of the water-sensitive in-situ ultrafast self-gelling hemostatic powder according to any one of claims 1 to 5 in the preparation of external-use medicines with hemostatic effects.
Citation Information
Patent Citations
Hemostatic, antibacterial and healing-promoting hydrogel with real-time monitoring function and preparation method
CN114920956A
Preparation method and application of body temperature induced adhesive gelatin-based hydrogel
CN116515134A
Rapid hemostatic gel and veterinary needle with rapid hemostatic gel coating and preparation method thereof
CN109260506A
Double-component quick blood-stopping medical adhesive and preparation method thereof
CN110935058A
Topical hemostatic powder composition and preparation method therefor
WO2022019467A1